تأثير المستخلص القلويدي (الرافايول) لنبات الفجل Raphanus sativus L. في مجموعة من البكتريا المرضية - م. تغريد نواف أحمد; م. ضحى جاسم; م. بشرى دلي حمد (University of Mosul-college of Basic Education, 2017)
The current study has contained inhibition effect test of alkaloid extraction of Radish (Raphiol) and Antibiotics such as: Amoxycillin+ Clavlanic acid (AMC), Doxy cycline (DO), Ciprofloxacian (CIP), TrimeThoprin + Sulphameuo xazol (SXT) against several types of The positive and negative Gram Disease bacteria which is 1- Salmonella typhi. 2- Esherichia coli. 3- Bacillus Subtilis. 4- Staphylococcus aureus. Which are considered of the wide spread Germs causing many effective diseases. The inhibition effect has been identified by sensitivity test (diffusion method by disks) depending on the method (Bauer et al, 1966), showing that alkaloid (Raphaiol) extracted from Radish has different inhibition effect according to the difference of the used part and the type of bacteria. It has been showed by the study that the concentrations of alkaloid extraction (Raphaiol) of Radish seeds (50, 100, 200) mg/ml showed evidently effect in growth inhibition of each positive and negative gram bacteria such as Staphylococcus aureus and Esherichia coli and their effect is more obvious than the used antibiotics widely. As well as it has showed that the alkaloid extraction of Radish of explants (Root) has negative effect in all growth (Esherichia coli, Staphylococcus aureus) concentrations (50, 100, 200) mg/ml. The extraction of callus leaves and roots of Radish have shown distinctive concentration (200) mg /ml in effective on inhibition growth of the bacteria Salmonlla typhi.